Cross-cultural adaptation, reliability and validity of the Spanish version of the long-term quality of life questionnaire - León-Salas, Beatriz; Bilbao-González, Amaia; de Pascual y Medina, Ana María; Esteva, Magdalena; Toledo-Chávarri, Ana; Fuentes-Sánchez, Claudio; Bohn-Sarmiento, Uriel; Padrón-Peña, Pilar; González-Sánchez, Sonia; Valcárcel-López, Rafael; Trujillo-Martín, María del Mar (Frontiers in Oncology, 2024)
The aim of this study was to translate, culturally adapt, and evaluate the psychometric properties of the Spanish Long-Term Quality of Life (LTQL) questionnaire.The LTQL was initially translated into Spanish and cross-culturally adapted based on established guidelines. The Spanish LTQL was administered to patients with breast cancer who had completed their initial treatment 5 years earlier, along with other self-report measures: Quality of Life in Adult Cancer Survivors (QLACS), Hospital Anxiety and Depression Scale (HADS) and EORT-QLQ-BR23. Reliability was evaluated using internal consistency and test-retest. Convergent and known-groups validity were examined. Structural validity as determined by confirmatory factor analysis (CFA) and Rasch analyses was used to assess the unidimensionality and item-functioning of the LTQL domains.Results: Cronbach's alpha were above 0.7 in all domains. Test-retest coefficients were between 0.72 to 0.96 for LTQL domains.LTQL total score was correlated with others total scores of other measures: QLACS (r=-0.39), HADS depression (r=-0.57), HADS anxiety (-0.45) and EORTC-QLQ-BR23 (r=-0.50). CFA provided satisfactory fit indices, with RMSEA value of 0.077 and TLI and CFI values of 0.901 and 0.909, respectively. All factor loadings were higher than 0.40 and statistically significant (P<0.001). Rasch analysis showed that Somatic Concerns domain had 4 misfitting items, and Philosophical/Spiritual View of Life and social Support domains only 1 misfit item. However, unidimensionality was supported for the four domains.